Navigating Empowerment: Transforming Healthcare Access for Migrant Women through Health Navigation - Komalasari, Rita; Mustafa, Cecep (Buana Gender: Jurnal Studi Gender dan Anak, 2025)
This study for the first time presents the multifaceted role of health navigation in empowering migrant women, reducing social isolation, and enhancing access to essential services. This research seeks to fill gaps in the literature by investigating the theoretical mechanisms of health navigation, analyzing the relationship between health navigators and migrant women, and assessing the impact of health navigation on healthcare access. The study also aims to provide insights into policy and advocacy implications for a more equitable healthcare system. A narative review was conducted to establish the theoretical foundations of health navigation. The findings underscore the importance of cultural sensitivity and shared experiences in health navigation, enhancing empowerment and trust between navigators and migrant women. The multifaceted impact of health navigation is demonstrated, including increased healthcare knowledge, reduced social isolation, and improved access to community services. Challenges faced by both navigators and migrant women are acknowledged. Importantly, the study highlights the potential for policy change and advocacy efforts to create sustainable, equitable healthcare systems. In conclusion, this research contributes novel insights into the role of health navigation in addressing healthcare disparities for migrant women.